Effects of Fitness Training Intervention On Strength and Endurance of Upper and Lower Extremities of Aged Men - Banerjee, Asoke; Chatterjee, Saikot; Roy, Uttam; Kumar Singh, Deepak; Manna, Snehasish; Khatun, Jinnatunnesa (Journal of Neonatal Surgery, 2025)
Aged men are the valuable sections of the society. They are the guardians as well as the sources of knowledge and experiences. Despite all enriched qualities they are the most vulnerable sections suffering from diseases and susceptibilities. Sometime get less importance in the society and remain as a marginalized group. So far functional fitness is concerned they are in the back seat. Many researchers are of the view that aged men of our country mostly bear functional fitness status at below average level. As the Indian population over the age of 60 years continues to grow, there will be rise in the level of functional disability. The level of functional fitness depends on an individual’s lifestyle inclusive of level of physical activity and health status. With advancing age the elderly population faces enormous challenges to maintain physical and cognitive function, quality of life and functional independence. The aging process and the physical inactivity alter functional fitness indicators. Physical inactivity to a great extent is the cause of the changes in functional abilities during the aging process (Nadel & Di Pietrol, 1995). Keeping in view the importance of aged men in the society and their vulnerable state with respect to health and fitness the scholar planned to conduct the study entitled “Effects of fitness training intervention on strength and endurance of upper and lower limbs of aged men”. To accomplish the study the scholar involved 50 aged men within the age group 60 to 65 as volunteers of his study. He employed chair stand test and arm curl test for assessment of strength and endurance of the upper and the lower limbs. based on the results of the pre and the post tests he arrived at the conclusion that both the strength and the endurance of the upper and lower extremities developed significantly due to the fitness training intervention.